AUTOIMMUNE OOPHORITIS AND THEIR CORRECTION BY GLUCOCORTICOIDS - T. V. Tupitsyna; S. V. Logvinov; O. A. Tikhonovskaya; M. L. Dmitrieva (Бюллетень сибирской медицины)
Autoimmune oophoritis (AO) is characterized by damage of generative and endocrine elements of the ovaries and leads to the formation of secondary insufficiency of the gonads. A question about the use of glucocorticoids (GC) for the correction of AO remains debatable.Objective: to study the electron-microscopic changes of structural-tissue cells in autoimmune ovariano ophoritis and after its correction by glucocorticoids in the experiment.The material. The experiment was performed on outbred white Mature rats-female. The main group of animals (12 rats) were simulated AO by intra-peritoneal introduction of antigens of ovarian. At 5th day prednisolone was injected to rats («Nycomed», Austria) in the dose of 3 mg/kg of body weight intramuscularly 14-day course. A comparison group (12 rats) were the animals with the model AO no course Ledger therapy. Controlintact rats (6 animals). Taking of the material was carried out by the 20th and the 60th day.Methods. The study of the ultrastructure ovaries were performed using transmission electron microscopy. The material was fixed 2.5% glutaraldehyde, postfixed in 2% solution of osmium tetroxide, dehydrated in ethyl alcohols rising concentration and placed in a mixture of resins Epon-Araldite. Sections were prepared on Ultrotom III (LKB, Sweden). To view the drugs used an electron microscope JEM-7A (Japan). Results. On the 20th day of the pilot AO there are significant ultrastructural changes of vessels, concerning mainly endothelial layer. Degenerative and destructive changes affected endocrinocytes in the composition of the libraries and granular, овоциты majority of antral follicles. The 60-day pathologic processes involved and preantral follicles in the medulla develop perivascular fibrosis-sclerotic changes. Holding GC therapy on the 5th day AO reduces ultrastructural breach the walls of blood vessels, limits migration of immune cells in the home defeat on the 20th day. By the 60th day in the conditions of the restored the blood tissue transport is the formation of full-fledged generative elements, confirmed by the results of electron microscopy study.Conclusion. The obtained experimental data are demonstrated the therapeutic efficacy of the GC-therapy in the early stages of AO.